2016
DOI: 10.1016/j.envres.2015.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Tracing fetal and childhood exposure to lead using isotope analysis of deciduous teeth

Abstract: We report progress in using the isotopic composition and concentration of Pb in the dentine and enamel of deciduous teeth to provide a high resolution time frame of exposure to Pb during fetal development and early childhood. Isotope measurements (total Pb and 208 Pb/ 206 Pb, 207 Pb/ 206 Pb ratios) were acquired by laser ablation inductively coupled mass spectrometry at contiguous 100micron intervals across thin sections of the teeth; from the outer enamel surface to the pulp cavity. Teeth samples (n=10) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 66 publications
0
5
0
Order By: Relevance
“…In this regard, the isotopic composition of blood Pb offers a potential way forward. Blood Pb values can be modelled using existing data for known anthropogenic sources (legacy leaded petrol, PM2.5-10 airborne particulates, coal ash, domestic and imported Pb ores used for the manufacture of in-house Pb pipes) (Hodgson et al, 2015;Shepherd et al, 2009Shepherd et al, , 2016. These will vary according to spatial and demographic factors but will provide an evidence-based isotopic framework for more informed public health intervention measures.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the isotopic composition of blood Pb offers a potential way forward. Blood Pb values can be modelled using existing data for known anthropogenic sources (legacy leaded petrol, PM2.5-10 airborne particulates, coal ash, domestic and imported Pb ores used for the manufacture of in-house Pb pipes) (Hodgson et al, 2015;Shepherd et al, 2009Shepherd et al, , 2016. These will vary according to spatial and demographic factors but will provide an evidence-based isotopic framework for more informed public health intervention measures.…”
Section: Discussionmentioning
confidence: 99%
“…While in situ isotopic studies of biological samples are limited [ 12 , 13 ], the potential for future studies looks extremely promising in mapping sample heterogeneity. For example, Pb isotopic analysis of teeth can be used to trace modern fetal and childhood exposure to lead [ 14 ], while secondary teeth can preserve isotopic signatures of geographic location, diet, and health in mummified human remains [ 15 ], demonstrating that recent advancements in ICP-MS, specifically the coupling of LA systems, have expanded an entire field of research.…”
Section: Applicationsmentioning
confidence: 99%
“…Dentin appears to continue to accumulate Pb after eruption of the tooth; therefore, dentin Pb is thought to reflect exposure that occurs up to the time the teeth are shed or extracted (Gulson 1996;Gulson and Wilson 1994;Rabinowitz 1995;Rabinowitz et al 1993). The technique of laser ablation-inductively coupled plasma-mass spectrometry (LA-ICP-MS) allows measurement of Pb levels in regions of dentin formed at various times during deciduous tooth formation in utero and after birth (Arora et al 2014;Shepherd et al 2016). Accumulation of Pb in dentin of permanent teeth may continue for the life of the tooth (Steenhout 1982;Steenhout and Pourtois 1981).…”
Section: Biomarkers Of Exposurementioning
confidence: 99%
“…Arora et al (2014) found that Pb levels in primary (prenatal) dentin were more strongly correlated with PbBs at birth (correlation coefficient, r=0.69, n=27), whereas Pb levels in secondary (postnatal) dentin were more strongly correlated with CBLI (r=0.38, n=75). Shepherd et al (2016) combined LA-ICP-MS with histological determinations of dentin age to reconstruct the history of incorporation of environmental Pb from various sources.…”
Section: Toxicokinetics Susceptible Populations Biomarkers Chemical Interactionsmentioning
confidence: 99%